2019
DOI: 10.1177/1062860618820687
|View full text |Cite
|
Sign up to set email alerts
|

An IDEA: Safety Training to Improve Critical Thinking by Individuals and Teams

Abstract: Errors in thinking contribute to harm, delays in diagnosis, incorrect treatments, or failures to recognize clinical changes. Models of cognition are useful in understanding error occurrence and avoidance. Intra-team conflict can represent failures in joint cognitive processing. The authors developed training focused on recognizing and managing cognitive bias and resolving conflicts. The program provides context and introduces models of cognition, concepts of bias, team cognition, conflict resolution, and 2 too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…There are limited data to suggest reflective practice as a clear evidence-based strategy to decrease our biases on a clinician-patient level but options such as cultural safety checklists and previously outlined strategies (Box 1) could provide support to coalface clinicians. [97][98][99] Better appreciation of biases in clinical reasoning could help clinicians reduce clinical errors and improve patient safety and provide better care for marginalised communities who have the worst healthcare outcomes. 106,107 It is hoped that the training would help bridge the gap from the unawareness of bias to the ability to recognise bias in others and within ourselves to mitigate personal biases and identify how discrimination may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data to suggest reflective practice as a clear evidence-based strategy to decrease our biases on a clinician-patient level but options such as cultural safety checklists and previously outlined strategies (Box 1) could provide support to coalface clinicians. [97][98][99] Better appreciation of biases in clinical reasoning could help clinicians reduce clinical errors and improve patient safety and provide better care for marginalised communities who have the worst healthcare outcomes. 106,107 It is hoped that the training would help bridge the gap from the unawareness of bias to the ability to recognise bias in others and within ourselves to mitigate personal biases and identify how discrimination may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinicians may find a practical checklist when providing healthcare in order to minimise their own biases when making decisions (Box 1). [97][98][99] The nature of decreasing bias through a singlefaceted intervention may be very difficult as bias is a 'wicked' or multi-faceted problem. 65 Unconventional methods of teaching bias may include a teaching bias to medical students in a non-clinical setting (such as a museum, a weekly series of case conferences examining health equity and implicit bias, and transformative learning theory).…”
Section: Evidence-based Bias Trainingmentioning
confidence: 99%
“…The complex clinical environment requires effective collaboration, communication, decision thinking, and competencies to handle conflicts. Critical thinkers bring to conflict situations abilities that promote win-win conflict resolution [30]. The strong positive correlation between CT and CMM may imply that our study provide a good foundation for further development of CT skills in the future.…”
Section: The Correlation Between Ct and Ei Cmmmentioning
confidence: 67%
“…Studies found that ineffective CMM on hospital units can undermine job satisfaction, group dynamics, and patient outcomes [27][28][29]. According to Browne et al [30], individuals with strong CT bring to conflict conditions skills that create a win-win conflict solution. Little empirical study, however, has looked at how CT skills are related to CMM in medical students.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 33 We envision this being done using a variety of modalities, but the most effective would likely be a multi-disciplinary simulation setting with a focus on debrief. 34 Future work is needed to incorporate these concepts into the education of each interdisciplinary department.…”
Section: Discussionmentioning
confidence: 99%